Not two numbers- the same number twice: 2.5 and 2.5. To find this out, use simultaneous equations: xy=6.25 and x+y=5. Rearrange the second equation to y=5-x and substitute this value for y into the first equation: x(5-x)=6.25. Expand the brackets to get 5x-x2=6.25, subtract 6.25 from both sides to get -x2+5x-6.25=0. Apply the quadratic formula to find the final answer.
I think first you calculate the area of the triangular face. If you forgot that's ok. The formula is A= bxh divided by 2 which is the same as the area of a triangle is base multiplyed by height and divided by two. Then you need to know the length of the prism(the length of the rectangle)and multiply them together. So your calculation should look like this: Triangular face- A=bxh divided by 2 let's say that the base of the triangle is 5 cm and the height is 12cm Length of prism- let's say the length is 25 cm A=bxh divided by 2 A=5 x 12 divided by 2 A = 20 divided by 2 A = 30 cm squared 30 x 25 = 750cm squared( little 2)
cos(x) = 1 - x2/2! + x4/4! - x6/6! + ... where x is the angle measured in radians.
The theorem uses a side called the "hypotenuse" this is the longest side of any triangle. The formula is x= nn + mm (x is the hypotenuse and n and m are the other sides) Lets say the sides were 3 and 4. x = 3x3 + 4x4 x = 9 + 16 x = 25. This is NOT the finished result, as we still have to SQUARE ROOT this. 25 square rooted is 5. So the sides are 3, 4 and 5
Arthur Pythagoras rules! 12 x 12 = 3 x 3 + x2, so x2 = 144 - 9 and x = sqrt 135 = 11.62 so to the nearest foot it reaches 12 feet (actually 11.62)
30
5(x2 - 25) 5(x + 5)(x - 5)
30
If x2 < 25 Then: |x| < 5 -5 < x < 5
3x4 plus 5x3 plus x2 - 5 divided by x 2 =[(3x4) + (5x3) + (x2 - 5)]/x2 =(12 + 15 + x2 -5)/x2 =(27 - 5 + x2)/x2 =(22 + x2)/x2
This can be factored in multiple ways, depending on the signs. X2+10x+25 factors into (x+5)2 or (x+5)(x+5). X2-10x+25 factors into (x-5)2 or (x-5)(x-5). If 25 is being subtracted, then the trinomial is impossible to factor.
x2 + 10x = 0 x2 + 10x + 25 = 25 (x + 5)2 = 25 x + 5 = +-5 x1 = 0 x2 =10
if x2 = 5 the value of x has to be 5 divided by 2 which is 2.5 x = 2.5
x2 - 10x + 25 = 0(x - 5)(x - 5) = 0x - 5 = 0x = 5
(x - 5)(x - 5)
x2−25
x^2 - 10 x + 25 = (x - 5)(x - 5)